Site-specifically labeled 89Zr-DFO-trastuzumab improves immuno-reactivity and tumor uptake for immuno-PET in a subcutaneous HER2-positive xenograft mouse model - Lotte K. Kristensen; Camilla L. Christensen; Mette Munk Jensen; Brian Agnew; Christina Schjöth-Frydendahl; Andreas Kjær; Carsten H. Nielsen (2019)
Antibody-based PET tracers are exceptionally well-suited for determination of the in vivo biodistribution and quantification of therapeutic antibodies. The continued expansion in antibody-based therapeutics has accordingly driven the development towards more robust conjugation strategies in order to reliably predict the performance of such agents. We therefore aimed to evaluate the effect of site-specific labeling by enzymatic remodeling on the stability, immuno-reactivity and tumor-targeting properties of the monoclonal antibody (mAb) trastuzumab and compare it to conventional, random labeling in a HER2-positive xenograft mouse model. Methods: Trastuzumab was conjugated with the p-SCN-Bn-Desferrioxamine (SCN-Bn-DFO) chelator randomly on lysine residues or site-specifically on enzymatically modified glycans using either β-galactosidase or endoglycosidase S2 prior to 89Zr radiolabeling. 89Zr-DFO-trastuzumab was injected into SK-OV-3 tumor-bearing NMRI nude mice. The antibody dose was titrated with either 100 µg or 500 µg of unlabeled trastuzumab. Mice underwent small animal PET/CT imaging 24, 70 and 120 hours post-injection for longitudinal assessment. Parallel experiments were conducted with an isotype control matched antibody. In vivo imaging was supported by conventional ex vivo biodistribution and HER2 immuno-histochemistry. Furthermore, site-specifically labeled 89Zr-DFO-trastuzumab was evaluated in a panel of subcutaneous patient-derived xenograft (PDX) models. Additionally, the affinity, in vitro stability and immuno-reactivity were assessed for all tracers. Results: Site-specific labeling significantly increased PET tumor uptake (One-way ANOVA, p<0.0001) at all time-points when compared to random labeling. Mean tumor uptakes were 6.7 ± 1.7, 13.9 ± 3.3 and 15.3 ± 3.8 % injected dose per gram tissue (%ID/g) at 70 hours post-injection, for random, β-galactosidase or endoglycosidase S2 labeled probes, respectively. Co-injection with unlabeled trastuzumab increased the circulation time of tracers but did not alter tumor uptake notably. Site-specific probes presented with a superior in vitro stability and immuno-reactivity compared to the randomly labeled probe. Ex vivo biodistribution confirmed the data obtained by in vivo PET imaging, and site-specific 89Zr-DFO-trastuzumab successfully detected HER2-positive tumors in PDX mouse models. Conclusion: 89Zr-DFO-trastuzumab is well-matched for specific immuno-PET imaging of HER2-positive tumors and site-specific labeling of trastuzumab by the SiteClickTM technology minimizes the impact of the DFO chelator on immuno-reactivity, stability and biodistribution. These findings support further development of site-specifically radiolabeled mAbs for immuno-PET.